Location of the Ankle Osteochondral Lesion of the Talus (OLT) Corresponding to the Anatomical Axis of the Tibia (Loading Axis) Crosses the Ankle Joint. Issue 1 (January 2022) - Sandberg, Maxwell L.; Mirghasemi, Seyed Alireza; Troiani, Zachary; Vaupel, Zachary M.; Fortin, Paul T.
Category: Ankle; Sports Introduction/Purpose: studies demonstrated that mechanical axis alignment affects the clinical outcome of the chondral repair surgery in the knee. Reduction in stress concentration around chondral defects with HTO has been found to favor cartilage repair in knee surgery. this study aimed to determine the relationship between the tibia mechanical axis alignment and OLT size and location. Methods: 57 patients that underwent OLT repair between 2016-2020 were included. X-rays and MRIs of the ankle were used to collect data on OLT in the study group. X-ray measurements included (a)-measured as distance from where vertical line through center of tibia crosses to center the talar joint in AP view (medial, lateral), (b)- measured as distance from where vertical line through center of tibia crosses to the center talar body in lateral view (ant, post). The coverage angle, TLS, TAS, MA, TI, TTI angles were measured. MRI measurements included distance of the edge of the OLT lesion from the center of the talar surface, in three plans, and for location of the OLT lesion based on the 9-zone grid system. Results: 37.3% of these patients had the mechanical axis of the joint cross posterolaterally, 15.6% anteromedially, 5.9% anterolaterally, and 3.9% posteromedially. 33.3% had the mechanical axis cross posteriorly along the midline of the lateral axis. Using the 9-zone grid to localize lesion location, lesions were most often seen in location 6 (37.3%), location 7 (21.6%), location 9 (21.6%), and location 4 (19.6%). Of note, 36.8% of patients with a posterolateral axis had lesions at location 6 and 26.3% at location 9. For patients with poster joint axis along the midline of the lateral axis, 47.1% had lesions at location 6 and 23.5% at location 7. There is a correlation between Lesion Surface Area and axis location in the AP view (Correlation coefficient: 0.301, P Value: 0.023). we found a significant difference for coverage angle (P<0.001), TLS (P<0.001), and TTI (P<0.001) for different groups. Conclusion: The significant correlation shows that the farther medial the location of the axis crosses the joint, the larger the surface area of the lesion. there is no significant difference between lesion length or area and location.